2016
DOI: 10.1590/1519-6984.13615
|View full text |Cite
|
Sign up to set email alerts
|

Centrocestus formosanus (Trematoda: Heterophyidae) in Melanoides tuberculata (Gastropoda: Thiaridae) from Vila do Abraão, Ilha Grande, Rio de Janeiro, Brazil

Abstract: Pleurolophocercous cercariae found in the invasive gastropod Melanoides tuberculata (Müller, 1774) collected in a stream of the Vila do Abraão, Ilha Grande, Angra dos Reis, Rio de Janeiro, Brazil were used for experimental infection that enabled the identification of the heterophyid trematode Centrocestus formosanus (Nishigori, 1924). The parasite has been found in the locality since 2007, after two years of the introduction of M. tuberculata. Recently, from a sample of 483 specimens collected in June 2013, 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 21 publications
0
9
0
4
Order By: Relevance
“…The occurrence of C. formosanus infection in zebrafish in Italy underlines the necessity to focus the attention on this invasive parasite, since this is the second case reported in the Italian peninsula [32]. Although its origin and distribution were initially restricted to Asia [4,[9][10][11][12][13]24,31], C. formosanus has been subsequently reported in other countries, including Europe [16][17][18][19][20][21][22]25,26,29,48]. Actually, to the authors' knowledge, this is the fourth case of C. formosanus infection in freshwater fish imported in Europe [19,32,40], confirming the introduction of this parasite in the European area, as well as the possible underestimation of this infection.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The occurrence of C. formosanus infection in zebrafish in Italy underlines the necessity to focus the attention on this invasive parasite, since this is the second case reported in the Italian peninsula [32]. Although its origin and distribution were initially restricted to Asia [4,[9][10][11][12][13]24,31], C. formosanus has been subsequently reported in other countries, including Europe [16][17][18][19][20][21][22]25,26,29,48]. Actually, to the authors' knowledge, this is the fourth case of C. formosanus infection in freshwater fish imported in Europe [19,32,40], confirming the introduction of this parasite in the European area, as well as the possible underestimation of this infection.…”
Section: Discussionmentioning
confidence: 99%
“…Within fish-borne trematodes, Centrocestus formosanus is a small heterophyid fluke, described for the first time in Taiwan [9] and widely distributed in Asia [4,5,[10][11][12][13][14][15]. Since the 1950s, several authors have reported this species in new continents, although its occurrence could still be underestimated [16][17][18][19][20][21][22]. C. formosanus, similar to other digenetic trematodes, exhibits a complex life cycle, as described by Nishigori [9].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations